Gaudium et Spes, Nostra Aetate, Dignitatis Humanae, and the opening of the Catholic Church to other religious traditions = Gaudium et Spes, Nostra Ætate, Dignitatis Humanae et l’ouverture de l’Église catholique à d’autres traditions religieuses = Gaudium et Spes, Nostra Aetate, Dignitatis Humanae e l’apertura della Chiesa Cattolica alle altre tradizioni religiose - Lefebure, Leo D. (Philosophy & canon law, 2016)
In three closely related documents, Gaudium et Spes, Nostra Aetate (Declarationon the Church’s Relation to Non-Christian Religions), and Dignitatis Humanae (Declaration on Religious Freedom), the Second Vatican Council called Catholics to dialogue and cooperation with all people of good will, including followers of other religious traditions. While the Catholic Church had always been concerned about the well-being of all humans, the Second Vatican Council launched a new era in Catholic relations with other religious traditions and with the entire human community. No earlier council had taken such dramatic steps to address all people of good will, to seek healing for past conflicts, to speak in positive tones about other religions, to affirm the religious liberty of all humans, and to move forward in collaboration with the entire human community. This essay explores this transformation.